TO ASSESS THE POSSIBILITY OF ENSURING THE QUALITY OF ELECTRICITY IN TERMS OF VOLTAGE DEVIATIONS OF CONSUMERS - N. V. Savina; N. S. Bodrug (Известия высших учебных заведений: Проблемы энергетики)
The article deals with the issue of assessing the possibility of ensuring the quality of electricity in terms of voltage deviation by consumers. The analysis of the characteristics of modern markets, energy and power. It is revealed that the transition of the new market economy is left without the possibility of regulating the voltage consumers, which are parties to retail markets. The order of an assessment of possibility of providing the required quality of the electric power on conclusions of electric receivers is offered and its realization on the example of real electric networks is shown. Recommendations were developed to address the problem of voltage regulation at the consumer.